Methodology for business process development in the digital economy in the formation of a sustainable industrial development mechanism - O. E. Astafyeva (Управление)
The article considers the methodology of business process development in the digital business transformation. The aim of the study was to determine the dependence of sustainable enterprise development on the organisation of stakeholder engagement in the context of the digital ecosystem and the organisation of effective digital asset management.Taking into account the aim of the study, the main objectives are to study international experience of managing business development in digital transformation, determine the impact of ecosystems on business organisation and management of business processes and sustainability, and develop recommendations for business model formation and its alignment with the ecosystem market needs.The study resulted in the development of a sustainability framework in the digital ecosystem and proposals for digital ecosystem configurations that focus on giving and generating “value” when applying new ways and methods of “platform” interaction in the digital economy. Sustainability in digital transformation and ecosystematic business organisation depends on how digital assets are managed and approaches used to resource management. This process requires consideration of the methodology for business process development and research into changes in the external environment, identifying the possibility of integrating actors into the digital ecosystem development processes and defining tools for business process management.